Alzheimer beta amyloid deposition enhanced by apoE epsilon4 gene precedes neurofibrillary pathology in the frontal association cortex of nondemented senior subjects - Yamaguchi, H; Sugihara, S; Ogawa, A; Oshima, N; Ihara, Y (Journal of neuropathology and experimental neurology, 2001)
To clarify how Alzheimer disease pathology develops in the brains of nondemented subjects, we examined the interrelations among the amounts and morphology of Abeta deposition, neurofibrillary pathology, and apolipoprotein E (ApoE) genotype in the frontal association cortex of 101 autopsy brains from patients aged between 40 to 83. Senile plaque density correlated well with the logarithmic data of insoluble Abeta measured by enzyme immunoassay (EIA). The amounts of Abeta42-ETA increased dramatically in the late preclinical stage, whereas the AP42+ plaque density increased in the early preclinical stage. Neurofibrillary pathology appeared only in the areas with severe Abeta deposition and in subjects aged over 70. The ApoE epsilon4 allele enhanced the Abeta3 deposition in presenile subjects. Plaque-associated glial Abeta was prominent in subjects with mild to moderate Abeta deposition. The morphology of cerebral Abeta deposition changed from diffuse plaques with small amounts of Abeta in each plaque in the early preclinical stage to primitive/neuritic plaques with larger amounts of Abeta in each plaque in the late preclinical stage. Our findings suggest that the prevention of Abeta deposition in the late preclinical stage can be a rational therapeutic target, especially in elderly people with ApoE epsilon4 allele.